TANTANGAN DAN PELUANG: PENDIDIKAN KARAKTER SEBAGAI PONDASI MENGATASI DEGRADASI MORAL DI ERA DIGITAL - Urifah, Dewi; Hayati, Mardiyah; Hasanah, Niswatun (Ibtida'iy : Jurnal Prodi PGMI, 2024)
The development of information and communication technology in the 21st century has had a significant impact on various aspects of life, including education. Primary school children, who are growing up in the digital era, face new challenges in managing information access and social interactions, which also influence their moral development. Phenomena such as cyberbullying and the spread of fake news add complexity to these issues. Therefore, character education that integrates moral values into digital interactions becomes crucial. This study aims to explore how character education can be adapted within the digital era to address the moral challenges children face. The research method used is a qualitative approach with a descriptive literature review. Data was collected from various sources, including journals, books, and articles relevant to the topic of character education and technology, with publication years limited to between 2016 and 2024. The findings show that the main challenge in character education in the digital age is the lack of curriculum integration that aligns with technological advancements. Furthermore, many educators and parents lack the knowledge and skills necessary to teach character values in a digital context. However, there are opportunities to use technology as a tool to strengthen character education, such as through educational apps and digital platforms. This research recommends updating the curriculum to include digital skills and online ethics, as well as providing ongoing training for educators and support for parents to enhance the effectiveness of character education in the digital age.